Non-Native Speakers’ Rhetorical Commonalities in Writing Script Introduction Section - Samad, Iskandar Abdul; Usman, Bustami; Rizkanisa, Novalia; Fitriani, Siti Sarah (Bina Nusantara University, 2018)
This research analyzed the rhetorical pattern (RP) of script Introduction section written by undergraduate students at four selected universities in Aceh. Information about the RP of introduction section had been found in literature, including the work of Indonesian students in general. However, specific information about the RP of the work of EFL students in Aceh was not determined yet. The main aim of the study was to explore whether Acehnese studentsperformed the exact pattern of written Academic English. Understanding the RP of this section was important because it helped readers to have a description of the whole script. A qualitative method was applied in this study to draw the RP through the content analysis. The data were taken from twenty undergraduate students’ scripts at four selected universities. CARS model was used to analyze all the data. In general, the result shows a unique RP of the Introductionsection by Acehnese students where RP of introduction section maintains the circular way of thinking.